Diffusion de technologies en agriculture climato-intelligentes (AIC) et état de l’autonomisation des femmes au Sénégal - Basse, Blaise Waly; Worou, Nadine (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This article identifies the impact of climate-smart technology (CST) adoption on women's empowerment in Senegal. Using data collected by AICCRA (2023) from 473 farming households in the Thies, Louga and Kaffrine regions, we used the index of Alkire et al. (2013) to apprehend the level of women's empowerment considering the five domains. The results of the propensity score inverse matching method reveal that the adoption of at least one AIC technology improves women's level of empowerment by 9.11%. Thus, the adoption of AIC technologies can be an effective economic policy instrument in the fight against poverty and the empowerment of women for inclusive development.